Nickel cobalt oxide-single wall carbon nanotube composite material for superior cycling stability and high-performance supercapacitor application - Lim, Mengfang (2013)
The electron conductivity of electrode material has always been a problem that hinders the practical application of supercapacitor. In this contribution, we report a facile synthesis of highly conductive nickel cobalt oxide-single wall carbon nanotube (NiCo2O4–SWCNT) nanocomposite by controlled hydrolysis process in ethanol–water mixed solvent. Ultrafine NiCo2O4 nanocrystals with a diameter around 6–10 nm are formed on the functionalized SWCNT bundles. This novel material not only exhibits a high specific capacitance of 1642 F g–1 within a 0.45 V potential range but also shows an excellent cycling stability of 94.1% retention after 2000 cycles at high mass loading. Our method provides a promising facile and high-performance strategy for supercapacitor electrode application.